The Creation of an Ideal Health Care System - Bosich, Paige (TRAILS: Teaching Resources and Innovations Library for Sociology, 2015)
The objective of this assignment is for students to critically analyze countries within the Bismarck, Beveridge, Out-of-Pocket, and National Health Insurance models to design their own ideal health care system.